Respostas

2014-03-11T23:41:33-03:00
A) 85 - 45 + 192 ÷ 4 + 11
 = 85 - 45 + 48 + 11
= 99

b)15 + 99 × (34 - 13 + 22 × 3)
= 15 + 99 × (34 - 13 + 66)
= 15 + 99 × 87
= 15 + 8613
= 8628

c)182 - 5 × (3 + 8) - (10 × 6 ÷ 12)
= 182 - 5 × 11 - (60 ÷ 12)
= 182 - 55 - 5
= 122

d) (4 × 72 - 34) ÷ 2
= (288 - 34) : 2
= 254 : 2
= 127

2014-03-11T23:44:37-03:00
A) 99
b) 15+99×(34-13+22×3)
    
15+99×(34-13+66)
    15+99×(34-79)
    15+99×45
    15+4455
    4470

c)182-5×(3+8)-(10×6÷12)
   
182-5×(3+8)-(60÷12)
   182-5×(3+8)- 5
   182-5×11- 5
   182-55- 5
    127-5
     122

d)(4×72-34)÷2 
   (288-34)÷2
    254÷2
    127